The Morphometrical and Histological Studies on The Pituitary Gland in Different Age Groups of goats (Capra hircus) - Nandeshwar, N.C.; Banubakode, S.B.; Charjan, R.Y.; Mainde, U.P.; Singh, Anand; Bhole, P.D.; Boddupalli, Ayesha (Indian Journal of Veterinary Anatomy, 2023)
Present work was conducted on, 36 healthy non-descript male and female goats, divided equally into 3 age groups as Group I (1-8 months), Group II (8-18 months), and Group III (18 months and above). Each group comprised 6 males and 6 females. The age of the animal was ascertained on the basis of dentition and then the animals were slaughtered. The pituitary gland of each animal was collected after the slaughter and brought to the laboratory for further processing.Morphologically there was a significant increase in weight, length, width, and thickness of the pituitary gland and histomorphologically there was a significant increase in the diameter of the cells of pars distaliswith the advancement of age in both males and females in all age groups.